DAMPAK PERUBAHAN ORGANISASI PEMERINTAH TERHADAP KOMUNIKASI ORGANISASI - Bayu Amengku Praja (Universitas Halu Oleo, 2021)
This study aims to see the impact of organizational change on communication organization, organizational climate, and organizational commitment on organizational perfomance within the Ministry Research Technology and Higher Education. Change of organization can have an impact on communication organization. This research uses research methods qualitative and post-positivist approaches. Respondent research as many as eleven sources consisting of eight resources persons are Kemenristekdikti employees and three sources outside of stakeholders. There is also a vision and mission from Kemenristekdikti as a reference for various work activities. As a consequence of the elaboration of this vision and mission, required planning and implementation of strategic steps a structured and measurable incorporation of Kemenristekdikti. In this case organizational communication is an aspect important in organizational change to produce a good working relationship with fellow employees. Because organizational communication can form a climate organizational communication, which will have an impact towards organizational commitment that also delivers impact on organizational performance.